Excess glutamate levels in the cerebrospinal fluid predict clinical outcome of bacterial meningitis - Spranger, Matthias; Schwab, Stefan; Krempien, Sebastian; Winterholler, Martin; Steiner, Thorsten; Hacke, Werner (Archives of neurology, 1996)
The clinical course of bacterial meningitis still is characterized by a high mortality and frequent neurological deficits in survivors. In addition to other potentially neurotoxic mediators of inflammation, the excitatory amino acid glutamate, which has been implicated in neuronal death in a variety of other neurological diseases, may also be involved in the pathological process of bacterial meningitis.To investigate the prognostic value of the glutamate concentration in the cerebrospinal fluid (CSF) of patients with bacterial meningitis.Thirty consecutive patients with bacterial meningitis were included in a prospective study. The clinical severity of the disease was assessed on admission and 14 days after the beginning of antibiotic treatment by means of the Glasgow Coma Scale. Studies of CSF were performed on admission and after 3 to 6 days. In addition to standard CSF investigations, including cell count, cytologic findings, protein analysis, glucose and lactate levels, and microbiological tests, the concentration of glutamate in the CSF was measured by an enzymatic assay.At admission, both CSF cell count and concentration of glutamate correlated well with the severity of the disease. After treatment, glutamate concentrations decreased significantly to normal or only slightly elevated levels in 23 patients. However, in 7 patients glutamate levels remained markedly increased. In this group, clinical outcome was significantly worse than in the group of patients with low glutamate levels in the second CSF analysis.A prolonged increase of glutamate levels in the CSF may predict poor clinical outcome in patients with bacterial meningitis, possibly because of the sustained neurotoxic effects of this excitatory neurotransmitter.